Impact of Income Expectations, Family Environment on Entrepreneurial Interests with Self-Efficacy as an Intervening Variable - Miftakul Alfan; Eka Hendi Andriansyah (IKIP Mataram, 2022)
The interest in entrepreneurship in UNESA Labschool High School students is very low, and employment is reduced due to the COVID-19 pandemic that is detrimental to most business people. This condition increases the number of unemployed people in Indonesia, one way to overcome this is to foster an interest in entrepreneurship since it was still in school in accordance with Presidential Instruction No. 9 of 2016. This study aims to determine the influence of income expectations, family environment, and self-efficacy on students' entrepreneurial interests. This study used quantitative methods and data collection using questionnaires with a total of 112 respondents. The data was processed with the WarpPLS application and with SEM analysis can determine the influence of self-efficacy variables able to mediate income expectation variables and family environment variables with significant results on entrepreneurial interest variables. The result of this study is that income expectations have a positive and insignificant effect on entrepreneurial interest, but indirectly (through intervening variables) have a positive and significant effect on entrepreneurial interest. The family environment directly has a significant and positive effect on the interest in entrepreneurship, the family environment indirectly has a positive and significant effect on the interest in entrepreneurship